PEMBERDAYAAN MASYARAKAT BERBASIS POTENSI LOKAL DI DESA MOMALA KECAMATAN DUNGALIYO KABUPATEN GORONTALO - Hanapi, Yayan; Antu, Anasrullah M.; Gobel, Ilham A.Van; Hamzah, Lisyen; Tolingguhu, Nurmaya; Ibrahim, Sabrawati; Messe, Semuel; Kadullah, Titi Nurwahyuni; Udju, Ulfadiyanti (Insan Cita : Jurnal Pengabdian Kepada Masyarakat, 2024)
Observation of the Momala village community was the first step taken by Gorontalo University community service work (KKP) students, which was more appropriate in the Momala village. The observations began by going around all the hamlets in Momala village. During our observations in Momala village, what we found was that the community's source of income was farming. So we students of the Community Service College (KKP) take one core program, namely making Moringa leaves into tea. Observation or observavi aims to design a community service work program, what are the shortcomings in Momala village so that we, Community Service Work College (KKP) students can implement the program according to the needs of the Momala village community.